Block versus longitudinal integrated clerkships: students' views of rural clinical supervision. Issue 7 (15th May 2018) - Witney, Martin; Isaac, Vivian; Playford, Denese; Walker, Leesa; Garne, David; Walters, Lucie
Abstract : Context: Medical students undertaking longitudinal integrated clerkships (LICs) train in multiple disciplines concurrently, compared with students in block rotations who typically address one medical discipline at a time. Current research suggests that LICs afford students increased access to patients and continuity of clinical supervision. However, these factors are less of an issue in rural placements where there are fewer learners. The aim of this study was to compare rural LIC and rural block rotation students' reported experiences of clinical supervision. Methods: De‐identified data from the 2015 version of the Australian national rural clinical schools (RCSs) exit survey was used to compare students in LICs with those in block rotations in relation to how they evaluate their clinical supervisors and how they rate their own clinical competence. Results: Multivariate general linear modelling showed no association between placement type (LIC versus Block) and reported clinical supervision. The single independent predictor of positive perception of clinical supervisors was choosing an RCS as a first preference. There was also no association between placement type (LIC versus Block) and self‐rated clinical competence. Instead, the clinical supervision score and male gender predicted more positive self‐ratings of clinical competence. Conclusions: The quality of clinical supervision in block placements and LIC programmes in rural Australian settings was reported by students as equivalent. Abstract : The effectiveness of apprenticeship‐style learning in rural hospitals is demonstrated through equivalence between block placements and longitudinal integrated clerkships.